(untitled) (Materiali di Estetica. Terza serie, 2017)
Throughout the history of culture, the utopia of creating a “double” has produced several relevant examples: from Filippo Negroli’s bourguignotte to the wax statues, from Baron Kempelen’s charming Turkish to the contemporary anthropomorphic robotics. But what is the element which allows us to categorize an artefact as kitsch? This question cannot be simply answered by referring to the intuitive judgement, according to which the kitsch would be nothing but an epxression of “bad taste”. This type of composition is always influenced by the human structural and unavoidable inclination to make copies. What is sure, then, is that the production of kitsch objects is steady, although it can be subject to change in relation to the new technologies and languages that are made available.